(untitled) (Revista Argentina de Cirugía, 2026)
The incidence of isolated pulmonary metastases in pancreatic ductal adenocarcinoma is about 13%. Resection of these metastases is uncommon; however, patients presenting only with pulmonary metastases have better survival compared to those with metastases on other locations. We report the case of a female patient who underwent lobectomy for metastases from pancreatic ductal adenocarcinoma. After resection, disease-free interval and specific diseases-free survival were 84 and 152 moths, respectively. We consider that the next step in the treatment of this subpopulation of patients is to select those patients with favorable tumor biology who would benefit from a more aggressive approach.